Yes, And co-creating value : case study: BotH₂nia hydrogen network - Franks, Kristina (2023)
The purpose of this thesis was to introduce improvisation theater’s Yes, And mindset as a truly human centric, real-time activity that is, as an inclusive, viable skill for co-creating value between and mutually for actors in a group dynamic. Passive or less pro-active actions lead to lower interaction and possibility for creativity and unexpected opportunities. The aim of the study was to help the Commissioner, BotH₂nia hydrogen network to understand what gave value to their member-actors in relation to the network service, in order to respond in a relevant and pro-active manner and towards future strategic development. The overall design process was guided by the Design Council Double Diamond and the literature review that aimed to define important theoretical areas of the thesis. The main hypothesis was "Yes, And co-creating value". The main areas included Yes, And, service-dominant logic value co-creation, design thinking and doing, and service design method and tools. Triangulation of mixed research methods, in particular the research methods observation and semi-structured contextual interviews, and service design tools empathy and service ecology maps were utilised during and after the conference, “BotH₂nia goes Luleå” where 145 participants came together to drive transition to clean hydrogen economies. Results of the research showed that key factors that influenced Yes, And happening in conference group activities could be observed, collected, and ordinally measured, and correlated with value topics raised in the participant interviews. A Yes, And rating scale showed that BotH₂nia network was applying a Yes, And approach already to 7 out of the 11 value topics. Results indicated that all theories complimented each other and helped validation, demonstrating also that value co-creation supported generic actors in an exchange, rather than persona influenced target groups. All aspects of the study culminated in three main Yes, And themes recommended to the Commissioner, which validated and supported further ...